A new species of the soft scale insect genus Tillancoccus Ben-Dov (Hemiptera: Coccomorpha: Coccidae) on coconut palm in Trinidad - Hodgson, Chris (Zootaxa, 2025)
A new species of Tillancoccus Ben-Dov, T. bendovi Hodgson (Hemiptera: Coccomorpha: Coccidae), on coconut palm from Trinidad is described and illustrated and a key is provided for separating the four species now known in the genus.